Multi-stakeholder Partner Value Chain Development A case of the Organic Pineapple in Ntungamo district, Western Uganda - Kalibwani, Rebecca Mutebi; Twebaze, Jennifer; Kamugisha, Rick; Kakuru, Medard; Sabiiti, Moses; Kugonza, Irene; Tenywa, Moses; Nyamwaro, Sospeter (Journal of Agribusiness in Developing and Emerging Economies, 2018)
The purpose of this paper is to demonstrate that agricultural commodity value chain development using multi-stakeholder partnerships (MSPs) can fast-track improvement in the livelihoods of rural farming households. With the view that such partnerships can raise farmers’ incomes, the study uses the case of the organic pineapple (OP) value chain in Ntungamo, Western Uganda, to understand the governance features that hold the value chain partners together, to analyse the costs and margins to the participating farmers, to identify opportunities for demand-driven upgrading of the farmers’ skills and knowledge, and the role that partnerships play in such upgrading.
Keywords: Governance; Value chain; Organic pineapple